Properties of Edible Films Based on Oxidized Starch and Zein - Elizabeth Argüello-García; Javier Solorza-Feria; J. Rodolfo Rendón-Villalobos; Francisco Rodríguez-González; Alfredo Jiménez-Pérez; Emmanuel Flores-Huicochea (International Journal of Polymer Science)
The objective of this work was to investigate the effect of zein and film formulation on mechanical and structural properties of native (FNS), and oxidized with 2.5% (FOSA) and 3.5% (FOSB) banana starch. The oxidized starch showed differences from native starch due to the oxidation process, showing a decrease in lipids, proteins, and amylose. The increase of the sodium hypochlorite increased the content of carbonyl and carboxyl groups in the ranges 0.015–0.028% and 0.022–0.031%, respectively. The film obtained from FOSB displayed the highest tensile strength (5.05 MPa) and satisfactory elongation value (27.1%). The zein addition caused a decrease in these mechanical properties, as well as a significant decrease in water vapour permeability (WVP). However, films from FOSA and FOSB showed higher permeability than that of the native starch. The addition of glycerol and the level of oxidation increased the films moisture. Micrographs showed that, during the oxidation process, impurities were largely eliminated from the starch granule, noting more homogeneous structures both in granules and films.